Pedagogical Concept of Self-reflection of Students of Social Education: Qualitative Study of Self-reflection Determinants - Jana Martincová* (RU Publications, 2021)
The main topic of the presented article is the pedagogical concept of self-reflection of students of Social Education. The authors understand the pedagogical concept as primarily educational determinants that influence and shape students’ self-reflection. To identify this aim, the authors formulate the main research question: How do social education students reflect on themselves as students, and what are the determinants of study self-reflection for social pedagogy students? The authors used the qualitative research strategy, specifically The Grounded Theory, through which sixty self-reflecting essays were analysed. These written self-reflections were further complemented with six in-depth interviews in which we acquired clarifying information on self-reflection and self-assessment of social education students. It was ascertained that students’ self-reflection is shaped through an awareness of internal and external study factors, which subsequently influence the overall concept of their study, motivation to perform, study style, and self-assessment.